Prevalencia de caries dental en primeras molares permanentes en escolares de 7 a 12 años en Piura - 2016 - Tió Fernández, Fabiola Rocío (2017)
ABSTRACT The purpose of the present study was to determine the prevalence of caries in first molars of permanent teeth in schoolchildren aged 7 to 12 years in private and state schools in the district of Piura in 2016. The present study was comparative and transversal, the total population was 4573 students and a sample of 688 students divided between the ages of 7 to 9 years and 10 to 12 years was obtained. The variables evaluated were dental caries in permanent first molars, using the CPOD, age group, genus and dental arcade, and the data were recorded in a diagnostic sheet prepared for the study. The prevalence of caries in the first permanent molars was 88.6%, with a high CPOD. According to the 10 to 12 year age group, the prevalence was 99.1%, with no significant difference with the 7 to 9 year age group. Regarding the gender, the prevalence of caries was 91.3% for the female gender, according to the statistical test there are significant differences in the prevalence of caries in both boys and girls. According to the dental arch, the lower one was the most affected with 82.2% and there is no statistical difference with the upper arch. With respect to the upper and lower arches it differs significantly when there are one or two impacted teeth.